Investigation of validity and inter examiner agreement of quantitative light induced fluorescent images in diagnosing cracked teeth - Sung-Ae Son; Yun-Hoa Jung; Jae-Hoon Kim; Jeong-Kil Park (Scientific Reports)
Abstract The images of the Quantitative Light induced Fluorescent (QLF) device, which provides both natural color images similar to those from intraoral cameras and fluorescent images using 405 nm light in a single shot, were evaluated for the validity and inter examiner reliability in detecting tooth cracks. QLF images of 26 cracked teeth before and after removing crack lines were taken. Two examiners assessed the QLF images before removing the crack line with natural color images, fluorescent images, and combination images showing both images simultaneously, and recorded the crack’s location after observing images. The reference standard of the crack’s location was established by a trained dentist based on QLF images after removing the crack line. The agreement between examiners and the reference standard of the crack line was calculated by kappa value. Inter examiner agreement of natural color images showed at 0.394, while fluorescent and combination images showed at 0.449 and 0.493. Compared with the reference standard, the combination and fluorescent images showed higher agreement at 0.742 and 0.662, while the natural color images showed the lowest agreement, at 0.164. Determining crack location using only natural colored QLF images is challenging, but fluorescent and combination images improved agreement between examiners and the reference standard.